Differentiate using first principle : e [under root(tan x)]

y = etanxLet δy be increment in y , corresponding to δx in x.So y +δy =etan(x+δx)Or δy  =etan(x+δx) - etanxDivide both sides by δx δyδx  =etan(x+δx) - etanxδxAs limδx0 δyδx =dydxSo dydx = limδx0etan(x+δx) - etanxδxOr limδx0etanx(etan(x+δx)-tanx - 1δx)Or  limδx0etanx(etan(x+δx)-tanx - 1δx)×tan(x+δx)-tanxtan(x+δx)-tanxOr limδx0etanx(etan(x+δx)-tanx - 1)tan(x+δx)-tanx×tan(x+δx)-tanxδxAs limx0ex-1x = 1


=etanx×lim                            δx0tan(x+δx)-tanxδxOr etanx ×limδx0tan(x+δx)-tanxδx×tan(x+δx)+tanxtan(x+δx)+tanx=  etanx ×limδx0tan(x+δx)-tanxδx×1tan(x+δx)+tanx=etanx ×limδx0sin(x+δx)cos(x+δx)-sinxcosxδx×1tan(x+δx)+tanx=etanx ×limδx0sin(x+δx)cosx-sinxcos(x+δx)δxcos(x+δx)cosx×1tan(x+δx)+tanx=etanx ×limδx0sin(x+δx-x)δxcos(x+δx)cosx×1tan(x+δx)+tanx=etanx ×limδx0sinδxδx×1cos(x+δx)cosx×1tan(x+δx)+tanx=etanx ×1cos2x×12tanx=etanx×sec2x×12tanx

  • 33
What are you looking for?